The effects of low-intensity pulsed ultrasound on fresh fracture: A meta-analysis. Issue 39 (September 2017) - Lou, Shenghan; Lv, Houchen; Li, Zhirui; Zhang, Licheng; Tang, Peifu
Abstract: Background: Low-intensity pulsed ultrasonography (LIPUS) is a form of mechanical stimulation that is delivered via a special device to the fracture site for the acceleration of fracture healing. We conducted a meta-analysis to assess the effect of LIPUS for fresh fractures in adults. Methods: MEDLINE, EMBASE and the Cochrane Library searched between Jan 1980 and Nov 2016. Studies should be quasi-randomized and randomized controlled trials (RCTs) comparing treatment with LIPUS to placebo or no treatment in adults with fresh fractures, reporting outcomes such as function; time to union; delayed union or non-union. Summary standard mean difference (SMD) and the risk ratio (RR) with their 95% confidence interval (CI) calculated with a random effects model. I 2 statistic was used to assess the heterogeneity. Risk of bias was assessed by the Cochrane risk-of-bias tool. The GRADE system was used to evaluate the evidence quality. Results: A total of 12 trials with 1099 patients were included. The pooled results showed that LIPUS significantly reduced the time to fracture union (SMD: 0.65, 95% CI: 1.13 to 0.17), improved the quality of life (SMD: 0.20, 95% CI: 0.03–0.37) without affecting the time to full weight bearing (SMD: 0.76, 95% CI: 1.92 to 0.4), the time to return to work (SMD: 0.06, 95% CI: 0.14 to 0.27), or the incidence rate of delayed union and nonunion (RR: 1.02, 95% CI: 0.60–1.74). Conclusions: Moderate-to-high quality evidence shows that LIPUS treatment reduces the time to fracture union and improves the quality of life without affecting functional recovery and incident rate of delayed union and nonunion, suggesting that LIPUS treatment may be a good treatment modality for adults with fresh fractures. However, there are some methodological limitations in the eligible trials, further studies are needed to determine the clinical circumstances under which LIPUS is truly valid and to examine the optimal approach for the use of this adjunctive therapy. Abstract : Supplemental Digital Content is available in the text